2021
DOI: 10.21203/rs.3.rs-576144/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eyes Compensate Smile When Wearing Mask

Abstract: The use of face masks has become ubiquitous. Although mask wearing is a convenient way to reduce the spread of disease, it is important to know how the mask affects our communication via facial expression. For example, when we are wearing the mask and meet a friend, are our facial expressions different compared to when we are not? We investigated the effect of face mask wearing on facial expression, including the area around the eyes. We measured surface electromyography from zygomaticus major, orbicularis ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Further, some eye-tracking studies reveal that the mouth area is more fixated during the recognition of happiness (Beaudry et al, 2014;Eisenbarth & Alpers, 2011). Though most studies show that mouth area is focused when happiness is detected (Blais et al, 2012;Kotsia et al, 2008;Eisenbarth and Alpers, 2011;Fischer et al, 2012), when Duchenne smiles are observed (Okazaki et al, 2021;Sheldon et al, 2021), eyes alone are diagnostic as Duchenne refers to smiles in which both the muscle that orbits the eye and Zygomaticus Major are active.…”
Section: Significance Statementmentioning
confidence: 99%
“…Further, some eye-tracking studies reveal that the mouth area is more fixated during the recognition of happiness (Beaudry et al, 2014;Eisenbarth & Alpers, 2011). Though most studies show that mouth area is focused when happiness is detected (Blais et al, 2012;Kotsia et al, 2008;Eisenbarth and Alpers, 2011;Fischer et al, 2012), when Duchenne smiles are observed (Okazaki et al, 2021;Sheldon et al, 2021), eyes alone are diagnostic as Duchenne refers to smiles in which both the muscle that orbits the eye and Zygomaticus Major are active.…”
Section: Significance Statementmentioning
confidence: 99%
“…Further, some eye-tracking studies reveal that the mouth area is more fixated during the recognition of happiness (Beaudry et al, 2014 ; Eisenbarth & Alpers, 2011 ). Though most studies show that the mouth area is focused when happiness is detected (Blais et al, 2012 ; Eisenbarth & Alpers, 2011 ; Fischer et al, 2012 ; Kotsia et al, 2008 ), when ‘Duchenne smiles’ are observed (Okazaki et al, 2021 ; Sheldon et al, 2021 ), the eyes alone are diagnostic, as the term Duchenne refers to smiles in which both the muscle that orbits the eye and zygomaticus major are active.…”
Section: Introductionmentioning
confidence: 99%